2018
DOI: 10.1007/s10928-018-9574-0
|View full text |Cite
|
Sign up to set email alerts
|

Guiding dose adjustment of amlodipine after co-administration with ritonavir containing regimens using a physiologically-based pharmacokinetic/pharmacodynamic model

Abstract: Amlodipine, a commonly prescribed anti-hypertensive drug, shows increased systemic exposure with cytochrome P450 (CYP) 3A inhibitors. Ritonavir (RTV) is a potent mechanism-based and reversible CYP3A inhibitor and moderate inducer that is used as a pharmacokinetic enhancer in several antiviral treatment regimens. Drug–drug interaction (DDI) between RTV and amlodipine is due to mixed inhibition and induction of CYP3A4, which is challenging to predict without a mechanistic model that accounts for the complexity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 44 publications
(66 reference statements)
1
21
0
Order By: Relevance
“…Boosted ARVs increase the exposure of calcium channel inhibitors due to inhibition of CYPs and thereby the hypotensive effect Start at a lower dose and titrate based on blood pressure response. Consider a 50% dose reduction for amlodipine and diltiazem Lercanidipine: contraindicated …”
Section: Discussionmentioning
confidence: 99%
“…Boosted ARVs increase the exposure of calcium channel inhibitors due to inhibition of CYPs and thereby the hypotensive effect Start at a lower dose and titrate based on blood pressure response. Consider a 50% dose reduction for amlodipine and diltiazem Lercanidipine: contraindicated …”
Section: Discussionmentioning
confidence: 99%
“…A physiologically based pharmacokinetic (PBPK) model study showed that a 50% reduced dose of amlodipine given with RTV was enough to maintain the same plasma level of amlodipine as with its full dose without RTV. The full dose of amlodipine can be resumed either immediately after stopping RTV or 5 days later under clinical monitoring [59].…”
Section: Lopinavir/ritonavir + Calcium Channel Blockersmentioning
confidence: 99%
“…Nifedipine [56,57], Amlodipine [58,59], Lacidipine , Cilnidipine, Diltiazem [58], Verapamil [63] Lercanidipine [61,39] Antiarrhythmic agents…”
Section: Calcium Channel Blockersmentioning
confidence: 99%
“…Then, the established nifedipine PBPK model was used to predict multiple dosing of nifedipine when co-administered with RTV-containing regimens. Since RTV is the only clinical inhibitor and inducer of CYP3A4 within the regimen, only RTV was simulated as a surrogate for the RTV-containing regimens [35]. In addition, the PBPK model of RTV has been already verified by simulating its inhibition effects on the PK profiles of CYP3A4 substrates [36].…”
Section: Nifedipine-rtv Ddi Predictionmentioning
confidence: 99%
“…In addition, it takes days of wash-out after RTV withdrawal to allow the nifedipine concentration to drop down to a safe level when patient taking nifedipine. These results are the important hints for patients taking the nifedipine treatment.The PBPK/PD analysis was once used to investigate dose adjustment recommendations for amlodipine during and after co-administration of RTV by Mukherjee, et al[35]. The analysis suggested that resuming a full dose of amlodipine…”
mentioning
confidence: 99%